Detailed Investigation of Downstream TLR Signaling in the Follicular Cells of Women with Endometriosis - R Jafari; SA Taghavi; E Amirchaghmaghi; R Salman Yazdi; L Karimian; M Ashrafi; R Aflatoonian (JRI, 2020)
Background: Inflammatory responses within the peritoneal cavity may result in endometrial dysfunction in women with endometriosis. The true causes of this disease remain poorly understood. It is hypothesized that downstream toll-like receptors (TLRs) inflammatory cytokines in response to pathogens may be associated with endometriosis. So, this study was aimed at evaluating the expression of TLRs signaling and endometriosis-associated inflammatory responses. Methods: Totally, 20 infertile endometriosis patients and 20 normal women undergoing controlled ovarian stimulation were enrolled. The cellular pellet and supernatant were obtained by centrifugation of follicular fluid (FF). Evaluation of TLRs and their signaling pathway gene expression was performed on cellular pellets using quantitative-PCR. The supernatant was used for determination of cytokine protein expression by ELISA. The results are expressed as mean±SEM and a p<0.05 was considered statistically significant. Results: Quantitative-PCR analysis suggested that TLR1, 5, 6, 7, 8, 10, MYD88, NF-ĸB, IL-10 and TGF-β genes expression significantly increased in patients compared to the control group (p<0.05). TLR3, 9, INF-β genes expression was significantly lower in endometriosis than control group (p<0.05). There was no significant difference in the expression of TLR2, TLR4, TIRAP, TRIF, TRAM, and IRF3 between two groups. Also, significant increase in the levels of IL-6, IL-8 and MIF protein in FF of endometriosis group was detected in comparison with normal women (p<0.05). Conclusion: The expression of TLR downstream signaling in the follicular cells can initiate inflammatory responses and changes in the FF cytokine profile which in turn may induce endometriosis and infertility disorder.